PERANCANGAN APLIKASI MOBILE UNTUK EDUKASI DAN PEMASARAN BERAS BERKELANJUTAN DI KABUPATEN DELI SERDANG - Yeni Rachmawati; Maulidya Rahmah; Cindy Wiranti (Smart Education, 2025)
Abstract: This study aims to design a mobile application as an educational and marketing media for sustainable rice farming in Deli Serdang Regency. The research uses a qualitative approach with surveys, interviews, and Focus Group Discussions (FGD) to gather data on sustainable farming and marketing practices of rice farmers. The results show that rice farmers in the area have not fully implemented sustainable farming principles, especially in environmentally friendly pest management and conventional marketing involving many intermediaries, which weakens farmers' bargaining position. The mobile application is designed to provide education on sustainable farming practices and direct market access to consumers, addressing digital literacy limitations through training and assistance. Thus, this application has the potential to enhance efficiency, farmer welfare, and support a digital transformation toward an inclusive and competitive agricultural system in Deli Serdang.Â Keyword: Mobile Application; Agricultural Education; Sustainable Marketing; Rice Farmers; Deli Serdang..Â Abstrak: Penelitian ini bertujuan merancang aplikasi mobile sebagai media edukasi dan pemasaran beras berkelanjutan di Kabupaten Deli Serdang. Metode yang digunakan adalah pendekatan kualitatif dengan survey, wawancara, dan Focus Group Discussion (FGD) untuk memperoleh data mengenai praktik pertanian dan pemasaran berkelanjutan petani padi. Hasil penelitian menunjukkan bahwa petani padi di wilayah tersebut belum sepenuhnya menerapkan prinsip pertanian berkelanjutan, terutama dalam pengendalian hama dan pemasaran yang masih konvensional melalui banyak perantara sehingga melemahkan posisi tawar petani. Aplikasi mobile dirancang untuk memberikan edukasi praktik pertanian berkelanjutan dan membuka akses pemasaran langsung ke konsumen, mengatasi kendala keterbatasan literasi digital petani melalui pelatihan dan pendampingan. Dengan demikian, aplikasi ini berpotensi meningkatkan efisiensi, kesejahteraan petani, dan mendukung transformasi digital sistem pertanian yang inklusif serta berdaya saing di Kabupaten Deli Serdang. Â Kata kunci: Aplikasi Mobile;Edukasi;Pemasaran Berkelanjutan; Petani Padi; Deli Serdang.